TOPOGRAPHIC ANATOMY AS A BASIS FOR MINIMALLY INVASIVE SURGERY - Suyunova Zamira Axatovna; Awaish Asim (TADQIQOTLAR, 2025)
Abstract The  advancement  of  minimally  invasive  surgery  has  transformed  clinical practice, reducing postoperative pain, hospital stay, and recovery time. However, the success  of  laparoscopic  and  endoscopic  procedures  largely  depends  on  precise knowledge of topographic anatomy. This article discusses the integration of anatomical principles into minimally invasive techniques and highlights their role in patient safety.